DNA ploidy and proliferating cell nuclear antigen in colonic adenomas: Can they predict recurrence - ÇELİKEL, ÇİĞDEM (My University, 1996)
To investigate the colonic adenoma-adenocarcinoma progression sequence, DNA ploidy analysis was performed on hyperplastic polyps to adenocarcinomas. DNA ploidy data were then compared with immunocytochemical staining for proliferating cell nuclear antigen (PCNA). In hyperplastic polyps to villous adenomas, all cases were diploid except one aneuploid villous adenoma. In three adenomas, diploid in situ adenocarcinomas were present. As diploid percentages decreased from hyperplastic polyps to villous adenomas, aneuploid percentages increased. In adenocarcinomas, the Dukes classification corresponded well to DNA ploidy status: all four stage A carcinomas were diploid, whereas three cases each of stage C1 and C2 carcinomas were aneuploid or multiploid. A surprising finding was that S-phase percentage in adenocarcinomas was not parallel with PCNA-positive tumor cell numbers. It is concluded that multistep adenoma-adenocarcinoma progression was partially reflected in DNA ploidy pattern from hyperplastic polyps to villous adenomas. In adenocarcinomas, the Dukes classification paralleled well the DNA ploidy status from stage A diploid to stage D aneuploid, but was not accompanied by increasing PCNA-positive cell numbers
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Gastroenteroloji-(Hepatoloji); Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Gastroenterology and Hepatology; Health Sciences; GASTROENTEROLOJİ VE HEPATOLOJİ; Klinik Tıp; Klinik Tıp (MED); GASTROENTEROLOGY & HEPATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Hepatoloji; Gastroenteroloji; Hepatology; Gastroenterology